DIVERSITY AND CORRELATION OF FOREWORD AND BACK LEGS BODY DIMENSIONS OF BALI CATTLE AT BALI CATTLE BREEDING CENTER GEROKGAK, BULELENG, BALI - Adinda, Adinda; Suatha, I Ketut; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2022)
This research was conducted on 25 cows at the Bali Superior Cattle Breeding Center in Gerokgak, Buleleng district. Data was collected by purposive sampling method and then processed using SPSS IBM 26 with descriptive and biplot analysis, then presented in the form of tables and biplot graphs. The results obtained indicate that the most varied coefficient of variance is the length of the upper foreleg of 22.8369%, then followed by the length of the upper hind leg of 19.3704%, the length of the middle hind leg of 17.1938%, the length of the forefoot the lower part obtained a score of 14.3102%, the length of the middle forefoot was 12.0132% and the most uniform was the length of the lower back leg of 10.6815%. The length of the lower hind legs is positively correlated with the length of the lower forelegs, the length of the middle hind legs is positively correlated with the length of the middle forelegs, as well as the length of the upper hind legs is positively correlated with the length of the front legs of the tatas, but the length of the middle forelegs negatively correlated with the length of the upper hind leg and between the length of the middle forefoot and the length of the upper hind leg was not correlated with the length of the upper forefoot. To get a uniform Bali cow, it is necessary to select the length of the upper forelegs.